The Effect Of Service Quality And Room Rates On Customer Satisfaction At Reddoorz Near Botani Square Mall Bogor Hotel - Kusumaningrum, Anisa Putri; Pradini, Gagih; Chandra, Muliyadi; Rahmawati, Ema; Kasmin (CV ODIS, 2023)
This study aims to determine how much influence the quality of service and room rates on customer satisfaction at Reddoorz Near Botani Square Mall Bogor Hotel. As well as to answer the formulation of problems regarding service quality and room rates to consumer satisfaction. The research method used is a descriptive and verification method with a sample of 100 people. Testing of research instruments uses validity and reliability tests. The data analysis method used is multiple linear regression analysis, multiple correlation, coefficient of determination and using SPSS Statistical tools Research results identified that Service Quality and Room Price have an influence on customer satisfaction Reddoorz Near Botani Square Mall Bogor Hotel